First detection of feline hemoplasmas in free-ranging jaguars (Panthera onca) - Furtado, Mariana Malzoni; Taniwaki, Sueli Akemi; Metzger, Betina [UNESP]; O'Dwyer, Lucia Helena [UNESP]; Paduan, Karina dos Santos [UNESP]; Almeida Jacomo, Anah Tereza de; Oliveira Porfirio, Grasiela Edith de; Silveira, Leandro; Sollmann, Rahel; Torres, Natalia Mundim; Ferreira Neto, Jose Soares (Elsevier B.V., 2018)
Species of hemoplasmas have been described worldwide, but little information is available for wild felids. Between February 2000 and January 2010, blood samples were collected from 30 jaguars (Panthera onca) and 22 domestic cats (Fells catus) from the Cerrado, Pantanal and Amazon biomes of Brazil. In all samples molecular tests were performed for Mycoplasma haemofelis/Mycoplasma haemocanis (Mhf/Mhc), 'Candidatus Mycoplasma haemominutum' (CMhm) and 'Candidatus Mycoplasma turicensis' (CMt). Twenty-two (73.4%) jaguars and four domestic cats (18.2%) tested positive for infection with at least one feline hemoplasma: 73.4% jaguars from the three areas were positive for CMhm, 13.6% jaguars from the Pantanal and 50.0% from the Amazon were positive for Mhf/Mhc, and 9.1% of individuals from the Pantanal tested positive for CMt. Domestic cats from the Cerrado (28.6%) and the Pantanal (30.0%) were positive for feline hemoplasma. All but one jaguar from the three sites are healthy. One female adult jaguar showed low body weight and dehydration. This is the first record of feline hemoplasmas in free-ranging jaguars. The high prevalence of CMhm suggest the participation of jaguars in the maintenance of this hemoplasma in nature. Although susceptible to Mhf/Mhc and CMt, jaguars did not appear to participate in the maintenance of these agents in the environment. The involvement of domestic cats in the transmission of any of these hemoplasmas cannot be excluded.
Keywords: 'Candidatus Mycoplasma turicensis'; 'Candidatus Mycoplasma haemominutum'; Conservation Medicine; Hemoparasites; Mycoplasma haemofelis; wild felids